HUBUNGAN MINAT BELAJAR DENGAN KEMATANGAN PEMILIHAN KARIR PESERTA DIDIK KELAS XI FASE F DI SEKOLAH MENENGAH ATAS NEGERI 1 BONJOL - Ramadani, Ramadani; Chandra, Yasrial; Mulyani, Rila Rahma (STKIP Pesisir Selatan, 2025)
This research is motivated by student behavior problems such as the presence of students who lack attention in following lessons, the existence of students who have low motivation to do assignments, and the existence of students who do not have a clear learning direction or goals. This study aims to find out 1). Describe the learning interests of class XI phase F students at SMA N 1 Bonjol. 2). Describe the maturity of career selection of class XI phase F students at SMAN 1 Bonjol. 3). Testing the relationship between interest in learning and the maturity of career selection of class XI phase F students at SMAN 1 Bonjol. This study uses a quantitative approach with a correlational design. The research population was all students of class XI phase F, with a total of 313 with a simple random sampling technique or random sampling which produced a total of 175 respondents according to the research criteria. The results of the analysis showed that there was a significant relationship with a value of -0.202 < of a p-value of 0.007 with a weak correlation level. Based on these results, it is recommended for students to continue to increase their interest in learning in the maturity of career selection in order to support success in the learning process. For guidance and counseling teachers to continue to encourage and motivate students to be able to increase their interest in learning and the maturity of career selection in the school environment.